THE ECOLOGICAL BENEFITS OF ROOFTOP GARDEN FOR BETTERMENT OF LOCAL URBAN HABITAT IN MALAYSIA - Mohd Raid, Maryanti; Azizan, Muhammad Uzair; Hussin, Khadijah; Megat Abd Rahman, Megat Mohd Ghazali (Journal of Technology Management and Business, 2017)
Rooftop garden is a modification of modern landscape which has the potential to be part of urban greenery system. Therefore, this article attempts to analyze and highlight its environmental benefits which able to solve environmental issues effectively and potential to be part of urban greenery system in Malaysia. An in-depth interview with seven experts in subject matter was conducted to justify the significant impact of this landscape. Based on the findings, all the respondents agreed that rooftop garden can assist city to solve several environmental issues effectively. However, the function and purpose of the landscape should be considered during the design and construction stage so that it can fully attain its objective whether as passive recreational facilities or as for environmental purposes. It is hoped that the research information from this article is useful to encourage its implementation and able to intensify the provision urban green space in Malaysia. Indirectly, it will assist urban area to create a healthy living environment and a balanced between the physical development and preservation of urban green space in the city.Â